Escape to Freedom - Simon, Barbara Brooks; Nang Chan Yeema (United States of America National Geographic Society, 2004)
An account of two slaves who escaped from their masters in Kentucky and, aided by the people of Underground Railroad, made their way to freedom in Canada.
Keywords: Juvenile Nonfiction